Restoring degraded soils: The transformative impact of Fanya Juu terraces on soil characteristics in the erosion-prone Magera watershed, Southern Ethiopia - Fekadu Fanjana Falta; Selemon Thomas Fakana; Nega Kesete Kassie (PLoS ONE, 2026)
Excess runoff-induced soil erosion significantly degrades farmland fertility, quality, agricultural productivity, and long-term sustainability. Although Fanya Juu terraces are widely implemented for mitigating these effects, previous studies rarely examined how slope position and conservation age influence soil recovery, as they focused on broad effectiveness. This study addressed the gap by analyzing soil characteristics across slope position and Fanya Juu structures of 5 and 10 years, compared with non-conserved land, to provide nuanced guidance for implementation. Soil samples (0–20 cm depth) were collected from 27 plots (3 slope positions x 3 treatments x 3 replications) in the watershed during the fall season of 2024. Normality and homogeneity of variance were assessed prior to analysis using the Kolmogorov-Smirnov and Levene’s tests, respectively. A two-way ANOVA and Tukey’s Least Significant Difference (LSD) test at a 5% probability level was used to analyze the data. The result revealed significant improvements with conservation age and slope position. Over ten years, Fanya Juu terraces have increased organic carbon (28%), total nitrogen (66%), available phosphorus (43%), CEC (39%), soil moisture (14%), silt (44%), and aggregate stability (51%) while reducing bulk density by 19%. The findings highlight that the Fanya Juu effectiveness depends strongly on slope and structure age, providing quantitative evidence for optimizing terrace design and long-term soil and water conservation planning in erosion-prone farmlands.